The memory of memorizers: a study of the memorization of Quran - Dzulkifli, Mariam Adawiah; Abdul Rahman, Abdul Wahab; Badi, Jamal Ahmed Bashier; Solihu, Abdul Kabir Hussain (2014)
The most influential research on people with superior memory performance in the Western literature focused mainly on chess players (Chase & Simon, 1973). In addition to greater body of knowledge, experts in a given domain have been found to possess accurate memory and superior ability to store information in memory. We have chosen to study the memory of Al Huffaz, i.e. those who memorize the Quran because of their exceptional memory performance to commit such a large volume of information in their memory. Although it has been agreed that storing and retrieving information from memory involves bidirectional transfer of information across multiple memory domains (Atkinson & Shiffrin, 1968, Cowan, 2000, Goldstein, 2011), there is less agreement on the nature of control processes that may become the basis for the information transfer. It is therefore the aim of the current study to investigate the memory control processes used by Al Huffaz. The findings from the interviews strengthened the involvement of several control processes such as rehearsal, motivation or interest and self-discipline. More importantly, it has been found that it is maintenance and not elaborative rehearsal that plays the most important role in memorization of the Quran. These findings will definitely help to form a better understanding on the cognitive basis underlying human memory, which will contribute to the planning and effort of the government to optimize the cognitive potential of its citizen to be productive in the nations development.